A Perylene Bisimide Organogelator for Chlorinated Solvents. Issue 2 (29th January 2014) - Lin, Xu; Hirono, Misaki; Kurata, Hiroki; Seki, Tomohiro; Maruya, Yukihiro; Nakayama, Ken‐ichi; Yagai, Shiki
Abstract Dye‐incorporated gel‐like materials are an attractive functional soft matter for optoelectronic applications. Chlorinated solvents are commonly used for the development of organic devices. Herein, we report that a perylene‐bisimide‐functionalized flexible bisurea can work as an efficient organogelator for several chlorinated solvents. The bisurea formed organogels in CHCl3 and 1, 1, 2, 2‐tetrachloroethane (TCE), but it gave viscous solutions in CCl4 at millimolar concentrations. UV/vis and fluorescence spectroscopies, atomic force microscopy, and transmission electron microscopy observation of the diluted solutions revealed that the bisurea forms soluble supramolecular polymers in CCl4 whereas it exists as monomeric or at least oligomeric species in CHCl3 and TCE at micromolar concentrations. These results suggest that differences in the aggregation process could explain the gelation behavior in chlorinated solvents. By using a viscous CCl4 solution, we fabricated top contact organic field effect transistors. The devices showed n‐type semiconductivity with a mobility of 1.5×10−5 cm2 V−1 s−1.